• Matéria: Matemática
  • Autor: vitotia90alcantara
  • Perguntado 6 anos atrás

materia-matematica ​

Anexos:

Respostas

respondido por: MarcosVaz
2

Resposta:

11

Explicação passo-a-passo:

A = x² + 8x + 9

B = 7x + 3x - 4(x + 1) = 7x + 3x - 4x - 4 = 10x - 4x - 4 = 6x - 4

A + B = (x² + 8x + 9) + (6x - 4)

A(-2) e B(3)

[(-2)² + 8(-2) + 9] + (6(3) - 4)

(4 - 16 + 9) + (18 - 4)

-3 + 14

11

respondido por: lucasamparo71
0

Resposta:

11

Explicação passo-a-passo:

A = x² + 8x + 9

B = 7x + 3x - 4(x + 1) = 7x + 3x - 4x - 4 = 10x - 4x - 4 = 6x - 4

A + B = (x² + 8x + 9) + (6x - 4)

A(-2) e B(3)

[(-2)² + 8(-2) + 9] + (6(3) - 4)

(4 - 16 + 9) + (18 - 4)

-3 + 14

11

Explicação

espero ter ajudado

Perguntas similares